Authentic Assessment in Physical Education - Akbar Syafruddin; Sufitriyono Sufitriyono; Agus Sutriawan (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
This study raised the phenomenon regarding the application of authentic assessment in the physical education learning process in Makassar City. This study aims to describe the application of authentic assessment both for the Affective, Cognitive and Psychomotor domains. The sample in this study were 10 physical education teachers in Makassar City. To obtain research data in this study carried out by observation, interviews, and documentation. The results of this study are that of the three domains of attitude, knowledge and skills in the application of authentic assessment, only one domain has not been implemented optimally, namely the assessment for the realm of attitude (affective), so that in the application of authentic assessment, the realm of attitude cannot be explained in detail. . Meanwhile, for the elaboration of knowledge (cognitive) assessment in the application of authentic assessment, each teacher has been able to describe and apply the concept of authentic assessment, although it is not as good as the application of authentic assessment for the assessment of the skill (psychomotor) domain, each psychomotor domain has been able to describe each student's skills into the authentic assesment.